Negara dalam Islam: Analisis Teoretis terhadap Tujuan dan Kewajiban Negara Menurut Al-Mawardi dan Abu Yusuf' - Halimatus Syakdiah (Universitas Pangeran Diponegoro Nganjuk, 2025)
The study of the concept of the state in Islam is an integral part of classical and contemporary Islamic political discourse. This article aims to systematically analyze the theory, objectives, and obligations of the state from an Islamic perspective by referring to normative literature (the Qur'an and Sunnah), the works of classical scholars such as Al-Mawardi and Abu Yusuf, and the thoughts of modern Muslim scholars such as Yusuf al- Qaradawi and Muhammad Asad. The method used in this study is a literature study with a normative-theological and historical-conceptual approach. The results of the study show that the state in Islam is not only a power structure, but also an instrument for implementing sharia and guarding the welfare of the people (ḥifẓ al-maṣāliḥ). The main objectives of the state include upholding justice, maintaining the five basic principles of maqāṣid al-sharī‘ah, and protecting the rights and obligations of citizens. The state is also obliged to carry out the functions of legislation, execution, distribution of social justice, and maintaining public order. This article concludes that the concept of the state in Islam is dynamic and can adapt to the development of the times as long as it adheres to the basic principles of sharia. The contribution of this article is expected to enrich the treasury of Islamic political thought and provide a normative basis for the formulation of state policy in a modern context.